SEMANTIC ANALYSIS OF PHRASES LINKED WITH “HEALTH” - Yuldasheva Dilfuza Shonazar qizi (Web of Journals Publishing, 2026)
Using semiotic analysis, this article identifies key cultural domains underlying the formation of phraseological units related to human vitality and well-being. The study establishes several semiotic areas that structure the semantic organization of phraseology: care, energy, abundance, endurance, youth, freshness, cheerfulness, and norm.
Keywords: Emiotic Analysis, phraseology, cultural domains, semiotic fields, iconic signs, human vitality, Health and Well-being, linguistic representation, Cognitive Semantics.